2017
DOI: 10.1371/journal.pone.0170143
|View full text |Cite
|
Sign up to set email alerts
|

Regional Homogeneity Changes in Nicotine Addicts by Resting-State fMRI

Abstract: ObjectiveTo reveal the brain functional changes of nicotine addicts compared with those of non-smokers and explore the objective biomarker for nicotine dependence evaluation.MethodsA total of 14 smokers and 11 non-smoking controls were recruited for this study. Resting-state functional magnetic resonance imaging and regional homogeneity (ReHo) were applied in the neural activity analysis. Two-sample t-test was performed to examine the voxel-wise difference between the smokers and the controls. Correlation anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
0
11
1
Order By: Relevance
“…Therefore, both BMI and CPD of MADs were higher than HCs. Although both CPD and BMI showed influence in ReHo and fALFF in several brain regions 47 , 85 , 89 91 , these alterations could not explain all the results in our study. Furthermore, we included BMI and CPD as covariates to control these effects in the analysis.…”
Section: Discussioncontrasting
confidence: 85%
“…Therefore, both BMI and CPD of MADs were higher than HCs. Although both CPD and BMI showed influence in ReHo and fALFF in several brain regions 47 , 85 , 89 91 , these alterations could not explain all the results in our study. Furthermore, we included BMI and CPD as covariates to control these effects in the analysis.…”
Section: Discussioncontrasting
confidence: 85%
“…Then we performed AFNI’s AlphaSim program 1 to correct for multiple comparisons. We ran 1000 Monte Carlo simulations with voxel-level p < 0.005, cluster size > 87, corresponding to a corrected p < 0.05 as determined by AlphaSim correction ( Yang et al, 2016 ; Chen and Mo, 2017 ). The FWHM of the individual t-maps was used as the Gaussian filter, along with a cluster connection radius of 5 mm, as previous studies have demonstrated that 1000 simulations are adequate for an fMRI study ( Brass et al, 2007 ; Chen et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…Chen et al. further found decreased ReHo in the superior frontal gyrus (SFG) and precuneus, and the decreased ReHo value in the precuneus was positively correlated with the Fagerström Test for Nicotine dependence (FTND) scores, an important index for clinical evaluation of smoker’s dependence on nicotine addiction ( 26 ). Using fractional ALFF technology, enhanced neural spontaneous activity was found in the caudate of young smokers ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of nicotine addiction, numerous rs-fMRI studies have focused on the properties of regional neural activity (12,(25)(26)(27)(28). For example, compared with nonsmokers, Yu and his colleague discovered that heavy smokers exhibited decreased ReHo in the prefrontal regions and increased ReHo in the insula and posterior cingulate cortex (PCC) (12).…”
Section: Introductionmentioning
confidence: 99%